A comparative investigation into novel cholesterol esterase and pancreatic lipase inhibitory peptides from cow and camel casein hydrolysates generated upon enzymatic hydrolysis and in-vitro digestion. (15th January 2022) - Mudgil, Priti; Baba, Waqas N.; Kamal, Hina; FitzGerald, Richard J.; Hassan, Hassan M.; Ayoub, Mohammed Akli; Gan, Chee-Yuen; Maqsood, Sajid
Highlights: Camel (CaCA) and cow casein (CwCA) hydrolysates demonstrated potential inhibition of cholestrolesterase (CE) and pancreatic lipase (PL) In-vitro digestion of the CaCA and CwCA hydrolysates showed significant improvement in inhibition of both PL and CE. Peptides MMML from CwC and AAGF from CaC were predicted to be one of the most active peptides against PL. Peptide LP found in both CwC and CaC hydrolysates was predicted to be active for CE inhibition. Abstract: Cow (CwC) and camel casein (CaC) hydrolysates were generated using Alcalase™ (CwCA and CaCA) and Pronase-E (CwCP and CaCP) each for 3 and 6 h, and investigated for their potential to inhibit key lipid digesting enzymes i.e., pancreatic lipase (PL) and cholesteryl esterase (CE). Results revealed stronger PL and CE inhibition by CaC hydrolysates compared to CwC. Potent hydrolysates (CwCP-3 h and CaCA-6 h) upon simulated gastrointestinal digestion (SGID) showed significant improvement in inhibition of both PL and CE. However, both the SGID hydrolysates showed similar extent of PL and CE inhibition and were further sequenced for peptide identification. Peptides MMML, FDML, HLPGRG from CwC and AAGF, MSNYF, FLWPEYGAL from CaC hydrolysates were predicted to be most active PL inhibitory peptides. Peptide LP found in both CwC and CaC hydrolysates was predicted as active CE inhibitor. Thus, CwC and CaC could be potential source of peptides with promising CE and PL inhibitory properties.